Inclusão sociodigital para atividades pedagógicas não presenciais em meio a pandemia de Covid 19: a experiência no IFES - campus Ibatiba com a utilização do programa auxílio emergencial de inclusão digital - Amorim, Danyllo Rodrigues de (2024)
As Information and Communication Technologies (ICTs) have been unevenly disseminated worldwide, debates have emerged regarding digital inclusion and exclusion, relating these terms to social inclusion. In this context, the concept of sociodigital inclusion has emerged, addressing actions aimed not only at infrastructure and access but also at the social advancement of individuals. In 2020, the impacts of COVID-19 pandemic affected the world in various ways, particularly in education, where face-to-face activities were urgently replaced by non-presential and distance activities. However, not all students had the same access conditions and the ability to use technological resources, as evidenced at the Federal Institute of Espírito Santo (Ifes) – Ibatiba Campus, where difficulties and access limitations, especially in rural and peripheral areas, hampered adaptation during the pandemic period. This qualitative and exploratory research analyzed and explain how the Emergency Digital Inclusion Aid, a program of the student assistance policy of Ifes, promoted the inclusion of the benefited students in the implementation of Non-Presential Pedagogical Activities (APNPs) during the pandemic. The resources used were identified, and the results obtained and the social impact generated were evaluated. Semi-structured interviews were conducted with the research subjects, and content analysis was applied to the transcribed data. Additionally, documentary research was carried out, involving documents and publications available from Ifes and Federal Government regulations. The main conclusions of the study revealed that, despite the challenges, the Emergency Digital Inclusion Aid was crucial in ensuring that many students could access and participate in the APNPs, reducing digital access inequalities during a critical time. However, the study also highlighted structural limitations and the need for more comprehensive and effective public policies to address educational and digital inequalities, especially in rural areas.